Evaluation of the Village Financial Information System (SISKEUDES) in Enhancing Governance and Financial Transparency in Indonesian Village Administration - Deni Danial Kesa; Ari Nurfikri; Cheng-Wen Lee (Khazanah Sosial, 2024)
This study analyses how Sistem Keuangan Desa (SISKEUDES, Village Financial System) can enhance trust, transparency, and good governance through user satisfaction and the net benefits of governance quality in the village context, focusing on information quality, system quality, and service quality. The research method used is path analysis, using path coefficient and t-statistics analysis. This study's primary data collection method is through surveys from the source. The questionnaires were distributed to respondents via email, direct contact person, and social media. Respondents were selected using a purposive sampling technique, with a total of 101 respondents. This result shows that the quality of information, systems, and services provided by the SISKEUDES application significantly affects user satisfaction and governance quality in village settings, enhancing trust, transparency, and good governance. These findings imply that reliable accounting information systems like SISKEUDES can improve the transparency and accountability of village fund management. This research contributes significantly to understanding the role of financial accounting information systems in improving village financial management and helping to create a more transparent and accountable environment at the village level. In addition, to address gaps in the literature or provide practical insights for policymakers or IT developers working on public sector financial systems.